2020
DOI: 10.3389/fmicb.2020.590851
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptomic and Proteomic Analyses Reveal the Role of NprR in Bacillus anthracis Extracellular Protease Expression Regulation and Oxidative Stress Responses

Abstract: NprR is a protein of Bacillus anthracis that exhibits moonlighting functions as either a phosphatase or a neutral protease regulator that belongs to the RNPP family. We previously observed that the extracellular protease activity of an nprR deletion mutant significantly decreased within in vitro cultures. To identify the genes within the regulatory network of nprR that contribute to its protease activity, integrated transcriptomic and proteomic analyses were conducted here by comparing the nprR deletion mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…GO terms with a value of p < 0.05 were identified as significantly enriched by DEGs. R scrip was used to estimate the meaningful statistical enrichment of the DEGs in KEGG pathways (Wang et al, 2020).…”
Section: Functional Annotation and Enrichment Analysismentioning
confidence: 99%
“…GO terms with a value of p < 0.05 were identified as significantly enriched by DEGs. R scrip was used to estimate the meaningful statistical enrichment of the DEGs in KEGG pathways (Wang et al, 2020).…”
Section: Functional Annotation and Enrichment Analysismentioning
confidence: 99%
“…This resulted in negative proteolysis of PNO2D1 (Figure 3C). Furthermore, nprR knockout in A16Q1 [21] showed that extracellular protease activity was greatly reduced in the deletion mutant A16Q1ΔnprR (Figure 3C).…”
Section: Nprr Mutation Resulted In a Nonproteolytic Phenotype And Dec...mentioning
confidence: 99%
“…Nontoxigenic encapsulated strain A16Q1 (pXO1 − , pXO2 + ) was obtained from toxigenic encapsulated strain A16 using plasmid incompatibility [20]. A16Q1∆nprR was an nprR-deletion strain constructed as per Wang et al [21,22].…”
Section: Strains and Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The B. anthracis V770-NP1-R strain used in AVA preparation is unencapsulated and has low protease activity [ 15 ]. Our previous work demonstrated that PA was upregulated and its degradation was inhibited in a mutant nprR -deficient B. anthracis strain [ 16 ]. Therefore, we hypothesized that a reduction in protease activity could mitigate the degradation of multiple known and unknown antigens secreted by the vaccine strain.…”
Section: Introductionmentioning
confidence: 99%